MARCH2 regulates autophagy by promoting CFTR ubiquitination and degradation and PIK3CA-AKT-MTOR signaling. Issue 9 (1st September 2016) - Xia, Dan; Qu, Liujing; Li, Ge; Hongdu, Beiqi; Xu, Chentong; Lin, Xin; Lou, Yaxin; He, Qihua; Ma, Dalong; Chen, Yingyu
ABSTRACT: MARCH2 (membrane-associated RING-CH protein 2), an E3 ubiquitin ligase, is mainly associated with the vesicle trafficking. In the present study, for the first time, we demonstrated that MARCH2 negatively regulates autophagy. Our data indicated that overexpression of MARCH2 impaired autophagy, as evidenced by attenuated levels of LC3B-II and impaired degradation of endogenous and exogenous autophagic substrates. By contrast, loss of MARCH2 expression had the opposite effects. In vivo experiments demonstrate that MARCH2 knockout mediated autophagy results in an inhibition of tumorigenicity. Further investigation revealed that the induction of autophagy by MARCH2 deficiency was mediated through the PIK3CA-AKT-MTOR signaling pathway. Additionally, we found that MARCH2 interacts with CFTR (cystic fibrosis transmembrane conductance regulator), promotes the ubiquitination and degradation of CFTR, and inhibits CFTR-mediated autophagy in tumor cells. The functional PDZ domain of MARCH2 is required for the association with CFTR. Thus, our study identified a novel negative regulator of autophagy and suggested that the physical and functional connection between the MARCH2 and CFTR in different conditions will be elucidated in the further experiments.